The Indonesian Constitution Read with German Eyes - Herbert Küpper (Constitutional Review, 2021)
The Indonesian Constitution offers many interesting insights to a German constitutional scholar. The most striking feature is the balance between the unitarian state and the natural diversity of Indonesia. In Germany, the state architecture reflects regional diversity in its federal framework, whereas Indonesia combines the unitarian state with various decentralising elements. This balance between unitarianism and regional diversity is probably the most conspicuous feature of the Indonesian Constitution and appears to be a suitable compromise between the conflicting aims of stabilising the state and the nation on the one hand and accommodating the geographic, demographic and cultural differences within the country on the other. Another striking feature is the presidential system, which is quite the opposite of the parliamentary system of the German Constitution. Other points that, from the perspective of German constitutional law, invite comparison are the constitutional provisions about the legal system,Indonesia’s constitutional monotheism, which is quite the opposite of the German idea of the state being strictly neutral in religious affairs, and human rights.